Reflections on higher education institutions responses intra-period COVID-19: A road towards a new normal in Arab universities - Asmaa Abusamra; Suyanto Suyanto; Sutrisna Wibawa (Institute of Advanced Engineering and Science, 2022)
While the unprecedented COVID-19 pandemic continues to impact, the new normal era becomes the latest universal issue to be discussed. Hence, most Arab countries are still categorized as developing countries, this stipulates the need to provide deep discussion on the typology of the types of responses currently undertaken by their higher education institutions. This can assess their agility in preparing for the intra-pandemic period and the unprecedented future disruption. This paper aims to give reflections on the adopted practices in Arab higher education institutions in response to COVID-19 disruption. It also aims to utilize the success indicators and challenges encountering these universities in a way to propose recommendations to shape the new normal era forward. In this study, a desktop analysis, leveraging six Arab universities websites and governments’ sources, was conducted wherein systematic literature, policy documents, as well as related procedures targeting COVID-19 and higher education were reviewed. The results indicate that, throughout the uncertainties of COVID-19, Arab higher education institutions continuously strive to deliver high quality of teaching and learning through employing consistent high-tech procedures entitling government legislations, education management, curriculum, scientific research and stakeholders’ collaboration.